Internal obesity as a risk factor for arterial hypertension - M. A. Druzhilov; T. Yu. Kuznetsova (Российский кардиологический журнал)
Aim. To assess the role of ultrasound parameters of the extent of abdominal and epicardial visceral adipose tissue (VAT) as prognostic tools for determining the probability of arterial hypertension (AH) development in normotensive patients with obesity.Material and methods. We studied 526 normotensive (according to the results of daily monitoring of blood pressure (BP)) men (age 45,1±5,0 years) without cardiovascular diseases and type 2 diabetes mellitus, with a SCORE risk <5% and abdominal obesity (waist circumference >94 cm). We analyzed glycemia, lipid spectrum, blood creatinine and urine albumin level. Echocardiography with an assessment of epicardial fat thickness (EFT), triplex scanning of the brachiocephalic arteries, ultrasound assessment of the thickness of abdominal VAT and subcutaneous fat (SCF) were carried out. At the end of the observational phase of the study (duration 46,3±5,1 months), repeated daily monitoring of blood pressure was performed.Results. Of the 406 available patients, hypertension was detected in 157 (38,7%), including 72 (31,7%) of the initial age group of 35-45 years and 85 (47,5%) of the initial age group 46-55 years. These patients were characterized by initially higher values of EFT (5,2±0,7 mm vs 4,4±1,0 mm, p<0,001) and the ratio of the thickness of abdominal VAT to the thickness of the SCF (2,9±0,6 vs 2,5±0,6, p<0,001). In the group of individuals with developed AH, the initial incidence of epicardial and abdominal visceral obesity was higher (58,0% vs 23,4%, p<0,001 and 44,6% vs 25,1%, p<0,001, respectively). Ultrasound parameters of abdominal and ectopic (epicardial) VAT were included in mathematical models of the probability of development of AH with a high level of statistical significance and maximum standardized coefficients of regression equations.Conclusion. Ultrasonic parameters of the severity of abdominal and epicardial VAT can be an additional tools for AH predicting in normotensive people with overweight and obesity.